Evolutionary psychology: theoretical foundations for the study of organizations - Mark Van Vugt (Journal of Organization Design, 2017)
This article provides an introduction to evolutionary psychology and its relevance to organizational design theory and practice. Evolutionary psychology assumes that human nature reflect adaptations to an ancestral environment that was intensely social, but differed profoundly from modern organizations in scale and complexity. Further, organizational structures and cultures co-evolved with human nature to deal with the different environmental challenges early humans faced. In this article, I present a concise review of the theoretical foundations of evolutionary psychology and convey how evolutionary psychology hypotheses about organizational design, culture, and leadership in organizations can be developed and tested. I also provide some directions for future research in this area and discuss implications for designing organizations that are perhaps better aligned with human nature than current structures.
Keywords: 650